HIV Care Nurses' Knowledge of HIV Criminalization: A Feasibility Study. (November 2016) - Phillips, Craig J.; Domingue, Jean‐Laurent; Petty, Mary; Coker, Michael A.; Howard, Terry; Margolese, Shari
Abstract : N/A: HIV‐related criminal laws in some jurisdictions may hamper population health efforts to manage HIV and bring about an AIDS‐free generation. HIV care nurses have an instrumental role to play in ensuring equitable care and health for all in a context of HIV. The purpose of our study was to determine HIV care nurses' knowledge of HIV‐related criminal laws. Ecosocial theory and content expert opinion guided development of a questionnaire to assess nurses' knowledge of HIV‐related criminal laws. A total of 174 HIV care nurses from Canada ( n = 23) and the United States ( n = 151) completed the questionnaire. Knowledge gaps were observed in several aspects of HIV‐related criminal laws that can influence nursing clinical practices. Nurses should increase their knowledge of HIV‐related criminal laws to ensure the success of population health initiatives and to reduce stigma and discrimination experienced by people living with HIV.